EXISTENCE OF HALAL TOURISM IN INDONESIA ISLAMIC BUSINESS ETHICS PERSPECTIVE: Existence; Halal Tourism; Islamic Business Ethics - Khutub, Muhammad; Ulfa, Ni'mah (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2022)
The purpose of this research is to find out how the existence of halal tourism in Indonesia perspectives islamic business ethics, the method used is a review literature with a type of qualitative research. The findings in this study that the existence of the halal tourism industry is not a threat to the existing tourism industry, but rather an addition to Muslim tourists, all of which do not hinder the ongoing progress of tourism. In fact, many countries in the world have worked on the halal tourism industry. According to the Mastercard Crescent Rating Global Muslim Travel Index (GMTI) in 2016, the total number of Muslim travelers worldwide reached 117 million in 2015. The results of this study and halal tourism are a process of integrating Islamic values into all aspects of tourism activities. The value of Islamic sharia into a religion or belief is embraced by Muslims as a basic reference in forming tourism activities using considering the basic values of Muslims in its presentation starting based on accommodation, restaurants, to activities. yang tourism always refers to Islamic norm.